Determination of bisphenol A, bisphenol F, bisphenol A diglycidyl ether and bisphenol F diglycidyl ether migrated from food cans using Gas Chromatography-Mass Spectrometry - I. Jordáková; J. Dobiáš; M. Voldřich; J. Postka (Czech Journal of Food Sciences, 2003)
Varnishes used for the inner coatings of food cans are mostly based on epoxy resins or vinylic organosols. The epoxy resins are produced from bisphenol A and bisphenol F and they also contain BADGE or BFDGE as stabilising components. A simple method for the quantitative determination of bisphenol A (BPA), bisphenol F (BPF), bisphenol A diglycidyl ether (BADGE), and bisphenol F diglycidyl ether (BFDGE) migrated from food packaging materials was optimised. The can sample was extracted with acetonitrile or with food simulants (distilled water, 3% acetic acid and 10% ethanol) and the extract obtained was analysed by gas chromatography coupled with mass spectrometric detector. The limits of detection and quantification ranged between 0.15-0.86 and 0.51-2.77 µg/dm2, respectively. The migrating levels of bisphenols found in various can samples were for BPA and for BADGE in the range from 0.63 × 10-3 to 0.34 mg/dm2, and from 1.49 × 10-3 to 3.67 mg/dm2, respectively. BPF and BFDGE were practically not detected in the can samples.